PENGARUH ENDORPHIN MASSAGE TERHADAP PENGELUARAN ASIPADA IBU POST PARTUM - Masning Masning; Firda Fibrilla; Martini Fairus (Jurnal Kesehatan Metro Sai Wawai, 2017)
Breastfeeding is good for infants. Expenditure breastfeeding is under the influence of various endocrine glands, especially the pituitary hormone prolactin and oksitosin. The coverage of exclusive breastfeeding in punggur areas health center, Lampung Tengah only 21.3 % than that specified by 80%. One of the efforts to help expenditure breastfeeding on the post partum mother arewith the methods and endorphin massage.Research purposes to know endorphin massage influence over outlays breastfeeding on the post partum in the Midwife private practicein the  working areas of health center punggur, Lampung Tengah. Thetype of the research is quantitative research. The design used quasi experimental design research static comparison group. The sample collection technique using nonprobabilitysampling method of sample with 34 people, which divided in the intervention group and control.The measuring instrument on this research using a checklist by means of measuring instrument observation. An analysis of the data used univariate analysis and bivariate uses mann whitney.The result of research shows that the expenditure brestmilk in endorphine message faster than the one which didn’t with 94,12% and the average expense is two days faster.Test results show of mann whitney p value worth 0,000 where the p value (0.05) so it can be inferred that there is the influence of androgen massage against expenditure on mother breast-fed post partum in the working area the midwife private practiceinpunggur health center, Lampung Tengah. The results of this research shows that endorphin massage expected to be used as non-farmakologis one alternative which safe and effective in efforts to overcome the expenditure on mother breast-fed post partum.